Capital Accumulation Process and Resilience: urban planning and redevelopment of port areas, a case study of Santos (Brazil) - Souza, Clarissa D. C. (International Planning History Society Proceedings, 2016)
The present work aims at outlining a current urban scenario of the urban planning implemented in the city of Santos (Brazil), especially the policies of urban and port requalification through the analysis of the actions of Alegra Centro Program. Alegra Centro is the name of the Revitalization and Development Program of the Historical Central Region of Santos. The program was created by the city government in February of 2003 and the analysis is focused on the last decade. The program is based on strategic actions and goals for development of the central area of Santos and its port. It also stimulates the resumption of economic development through actions in the following areas: improvement of the urban landscape; preservation and restoration of historical sites, artistic and landscape heritage; integration between the pier and the central area among others. Based on Harvey (2002) and others authors this paper identifies the process of capital accumulation and reproduction in the local space through the analysis of the developing urban requalification policy, therefore the resilience of the urban space (THACKARA, 2009), and its historical relationship in the process of the city urban planning. This work also deals with the transformations of the urban space of the city of Santos, from the physical and social point of view. It discusses the realized actions in the process of urban requalification and compares them with the ones taken towards housing policy. The proposal of the present work verifies that the project of requalification of Santos is indeed one that privileges the allocation of public resources in a strategic site of the city. Furthermore, would not the implementation of the urban requalification model be the adoption of “displaced ideas” (SCHWARZ, 1999) therefore the importation of models without considering the specificities, local reality and social fragilities? It discusses and concludes the following hypotheses: the proposal of requalification is more of an ideological rhetoric, which perpetuates the accumulation of capital, therefore the resilience of the urban space; the studied demonstrates the impact of the proposals in the urban dynamics and reality and its social issue. It confirms the thesis that the ongoing redevelopment project in the city of Santos is an urban policy that favors the allocation of public resources in strategic areas of the city, especially in the central area, for the benefit of private entrepreneurs. And finally it demonstrates the city plan or scheme that is being implemented in Santos, which is the allocation of public resources in the city central area as a public strategic that has been deepened the social issues without considering the local residents.